Differences in growth and development velocity between boys and girls from Kosovo, aged 6-18 years (International Journal of Medical and Surgical Sciences, 2020)
Background: Human growth and development is a complex process of bio-psycho-social changes in children and adolescents. The evaluation of these two processes is of high importance in clinical and anthropological contexts. The present study aimed to find out and to evaluate the velocity of the biological growth and development during different ages of Kosovo children and adolescents of both genders.Materials and methods: Body Height, Body Weight, and Ideal Body Weight were measured in 68762 children and adolescents from Kosovo (66264 boys, 2498 girls). Age groups were classified into 13 categories, ages 6.0-18.9 years old. There have been analyzed the systematic differences between males and females in the annual changing of Body Height, Body Weight, and Ideal Body Weight.Results: Based on the results of the present study growth and development in boys can be divided into three stages that are distinct from one another, compared with the girls' growth and development that can be divided into four stages. Boys have reached the Peak Height Velocity (PHV=7.8cm), respectively the Peak Weight Velocity (PWV=6.6kg) at the age-group of 14 years old, while girls have reached the Peak Height Velocity (PHV=8.4cm) and the Peak Weight Velocity (PWV=12.6kg) at the age-group of 11 years old.Conclusion: The puberty stage occurs approximately three years earlier in girls (11yrs) compared with the boys (14yrs). Although the boys experience a later achievement of PHV, their growth, and development, with reduced intensity, it continues even after the age of 18th. The girls' body growth and development commence earlier in age, and it reaches the maximal values earlier. This fact suggests that males will grow more during the late stage of the adolescence compared with females; therefore, in general males’ morphometric features tend to be larger.